Potential Therapeutic Applications of N-Cadherin Antagonists and Agonists - Blaschuk, Orest W. (Frontiers in Cell and Developmental Biology, 2022)
This review focuses on the cell adhesion molecule (CAM), known as neural (N)-cadherin (CDH2). The molecular basis of N-cadherin-mediated intercellular adhesion is discussed, as well as the intracellular signaling pathways regulated by this CAM. N-cadherin antagonists and agonists are then described, and several potential therapeutic applications of these intercellular adhesion modulators are considered. The usefulness of N-cadherin antagonists in treating fibrotic diseases and cancer, as well as manipulating vascular function are emphasized. Biomaterials incorporating N-cadherin modulators for tissue regeneration are also presented. N-cadherin antagonists and agonists have potential for broad utility in the treatment of numerous maladies.